1988
DOI: 10.1182/blood.v71.6.1641.1641
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of polyethylene glycol-tissue plasminogen activator adducts that retain functional activity: characteristics and behavior in three animal species

Abstract: Conditions were defined for the derivatization of recombinant tissue plasminogen activator (rt-PA) with polyethylene glycol (PEG) so as to retain functional activity as a possible means of producing a t-PA species with a prolonged circulating lifetime. Derivatives with a wide range of retention of activities were prepared by varying the concentration and species of activated PEG. The specific activities of the PEG-rt-PA derivatives were dependent on the method of assay. Assays using preformed fibrin gave highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

1992
1992
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(18 citation statements)
references
References 27 publications
1
17
0
Order By: Relevance
“…However, covalent attachment of PEG on the protein surface, ironically, often results in diminished drug activity because of steric hindrance created by PEG molecules that prevent the target molecule to interact and produce pharmacological action, as was the case with tPA. 22 Our proposed HSA-protamine conjugate is designed to address the above mentioned limitations in which the bulky albumin moiety will serve as a "camouflage" for the drug in the systemic circulation, whereas the positively charged protamine will facilitate formation of an electrostatic complex with the drug. Depending on the therapeutic application, a triggering agent can be chosen to disrupt the construct and liberate free drug at the site of action.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, covalent attachment of PEG on the protein surface, ironically, often results in diminished drug activity because of steric hindrance created by PEG molecules that prevent the target molecule to interact and produce pharmacological action, as was the case with tPA. 22 Our proposed HSA-protamine conjugate is designed to address the above mentioned limitations in which the bulky albumin moiety will serve as a "camouflage" for the drug in the systemic circulation, whereas the positively charged protamine will facilitate formation of an electrostatic complex with the drug. Depending on the therapeutic application, a triggering agent can be chosen to disrupt the construct and liberate free drug at the site of action.…”
Section: Discussionmentioning
confidence: 99%
“…The initial rate of hydrolysis of S-2251 by plasmin generated from plasminogen by tPA was determined by measuring the absorbance at 405 nm at different time intervals using a micro-plate reader (SynergyMx, Biotek). The slope of absorbance against square of time (DA min 22 ) was expressed as the initial rate of S-2251 hydrolysis. To assess heparin-mediated triggered release, the assay was also performed in the presence of 0.4 m/mL of heparin.…”
Section: Cytotoxicity Study Of Prepared Carrier Systemmentioning
confidence: 99%
“…40 Berger and Pizzo showed that PEGylated tPA circulates 10 times longer in mice, rats, and beagles than tPA, though the active half-life is only increased threefold because of inhibition by PAI-1 and PAI-2. 41 In all of these reports, the fibrinolytic rate of the PEGylated PA is slightly accelerated compared to the non-PEGylated control, likely due to reduced inhibition.…”
Section: Macromolecule Modific Ation Of Pl a S Minog En Ac Tivator Smentioning
confidence: 95%
“…glycol)-based modification (PEGylation) of fibrinolytic agents such as tissue plasminogen activator (tPA), streptokinase (SK), urokinase (UK), and staphylokinase (SAK) has been reported. [62][63][64][65][66] In some studies, it was found that the "protective" property of PEG-SK conjugates could be improved by increasing the molecular weight of PEG. 63 PEGylated systems of truncated SK variants with promising in vitro fibrinolytic activity and enhanced in vivo circulation residence time have also been reported recently, although the in vivo fibrinolytic capacity of these systems were not reported.…”
Section: Direct Modification Of Therapeutic Agentsmentioning
confidence: 99%
“…64 Recombinant tPA has also been conjugated to PEG and the PEG-tPA product was reported to show partial enhancement of circulation lifetime and bioactivity compared with free tPA in canine models. 62 The PEGylation strategy has also been reported for anticoagulant molecules. For example, PEG has been conjugated to the thrombin inhibitor hirudin and these PEG-hirudin systems have been evaluated in vitro, in vivo, and even in clinical studies in human patients.…”
Section: Direct Modification Of Therapeutic Agentsmentioning
confidence: 99%